Prawo zamówień publicznych w warunkach stanów nadzwyczajnych - Przeszło, Ewa (PRAWO i WIĘŹ, 2025)
Efficient spending of public funds is a crucial task for the state, even in times of particular threat and following the introduction of a state of emergency, whether martial law, a state of emergency, or a natural disaster. In such situations, it is essential to restore the state's normal functioning in the face of exceptional threats. Legal instruments and mechanisms specified in public procurement law can and should serve this purpose. Therefore, the aim of this study will be to demonstrate the extent to which public procurement and its legal frameworks align with the normative solutions of states of emergency and how they can be useful and utilized in such situations.